THE POTENTIAL OF POVERTY ALLEVIATION AND ECONOMIC INEQUALITY IN RURAL AREAS - Abd Kadir Arno (Al-Amwal : Journal of Islamic Economic Law, 2019)
This article aims to identify the potential for poverty alleviation programs and income inequality in rural areas globally in Indonesia as stated in Government Regulation No.11 of 2019, wherein article 100 paragraph 1 Village Expenditures stipulated in the ApBDesa are used for the implementation of village development, coaching Village community, and the empowerment of the Village community according to the local potential they have, so that the programs carried out must be in line with the needs of the village and its people